The Blackwell guide to feminist philosophy - Alcoff, Linda; Kittay, Eva Feder (Blackwell Pub., 2007)
The Blackwell Guide to Feminist Philosophy is a definitive introduction to the field, consisting of 15 newly-contributed essays that apply philosophical methods and approaches to feminist concerns. * Offers a key view of the project of centering women's experience. * Includes topics such as feminism and pragmatism, lesbian philosophy, feminist epistemology, and women in the history of philosophy.